2012
DOI: 10.1111/j.1600-6143.2012.04258.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Heart Allocation in the United States

Abstract: Lung and heart allocation in the United States has evolved over the past 20-30 years to better serve transplant candidates and improve organ utilization. The current lung allocation policy, based on the Lung Allocation Score, attempts to take into account risk of death on the waiting list and chance of survival posttransplant. This policy is flexible and can be adjusted to improve the predictive ability of the score. Similarly, in response to the changing clinical phenotype of heart transplant candidates, hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 24 publications
0
91
0
Order By: Relevance
“…10,11 Median survival for all OHT recipients is currently 10 years, increasing to 13 years conditional on surviving the first year. 10 More than 3500 people are currently listed for OHT, with a median wait-list time of 5 to 6 months, 12 although only 2200 OHT operations are performed annually in the United States, in part attributable to limited donor availability. 10,13 Randomized clinical trials involving patients with stage D heart failure have demonstrated improvements in survival among transplant-ineligible patients undergoing LVAD implantation as destination therapy (DT).…”
Section: Clinical Perspective On P 478mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Median survival for all OHT recipients is currently 10 years, increasing to 13 years conditional on surviving the first year. 10 More than 3500 people are currently listed for OHT, with a median wait-list time of 5 to 6 months, 12 although only 2200 OHT operations are performed annually in the United States, in part attributable to limited donor availability. 10,13 Randomized clinical trials involving patients with stage D heart failure have demonstrated improvements in survival among transplant-ineligible patients undergoing LVAD implantation as destination therapy (DT).…”
Section: Clinical Perspective On P 478mentioning
confidence: 99%
“…11,[16][17][18] The median wait-list time to receive a heart in the United States was 5.6 months based on the Scientific Registry of Transplant Recipients (SRTR). 12 In our model, we randomly generated a different wait-list time for each patient, such that the median wait time is 5.6 months. Under a constant hazard rate of an organ becoming available, this implies that 77% of patients receive a heart within 1 year.…”
Section: Survival Ratesmentioning
confidence: 99%
“…Allocation of organs to pediatric recipients uses the LAS system in patients 12 yr of age or older (Sweet 2009). For patients under 12 yrof age, the United States uses a two-priority system in addition to wait times (Colvin-Adams et al 2012). Patients meeting criteria (Table 1) are priority 1 and receive consideration for graft allocation first following geographic and blood-type criteria considerations.…”
Section: Pediatric Lung Transplantationmentioning
confidence: 99%
“…Over the last 50 years, lung transplant outcomes have continued to improve and the lung allocation system has evolved, with a goal to maximize the net benefit provided for all donated lungs. 4,5 Before 1995, the allocation process for lungs was solely based on wait-list time, geographic location, and blood type. 6 In 1995, a special exemption was made to allow for credit for an additional 90 days for patients with idiopathic pulmonary fibrosis (IPF) given their increased wait-list mortality; however, this did not account for variable mortality among other pulmonary diseases represented on the wait-list.…”
Section: Introductionmentioning
confidence: 99%